Physical health condition and physical organism readiness levels of sports veteran wrestlers - Гончаров, Алексей; Рубан, Лариса; Ананченко, Константин (Slobozhanskyi Herald of Science and Sport, 2017)
Oleksiy Goncharov, Larysa Ruban & Kostiantyn Ananchenko Purpose: study and an assessment of the physical state of health and the degree of physical fitness of the organism among active veteran wrestlers. Material & Methods: participants: 16 active veteran athletes, 7 of them judoka and 9 sambo wrestlers aged 36–45. Sports qualification of athletes: MS – 10 people, MSIC – 6 people. The stability of the organism to the conditions of hypoxia and hypercapnia was assessed by the results of the Stange and Genci tests. To determine the statistical balancing, the Bondarevsky trial was used. The degree of physical readiness was evaluated by the results of the distance traveled on the treadmill of Kettler, comparing it with the Cooper table. To assess the level of physical state, the formula was used by E. A. Pirogova. Results: investigation determined that the actions of the wrestlers – sports veterans of the body's resistance to the conditions of hypoxia and hypercapnia, as well as the indicator VC indices correspond young people. Indicators of statistical balancing among the acting veterans of judoists and sambo wrestlers corresponded to those of 20–30-year-old people. Level of physical condition (LPC) of health in 71,4% of veteran-judoists at the average level and only 28,6% is of a high level. Sambo veterans observed the following: 44,4% of sportsmen of the LPC are above the average; 33,3% have an average level of physical health; in 11,1% of athletes the average LPC and 11,1% of the judo veterans have indicators corresponding to the level below the average. Conclusion: conducted step-by-step medical and pedagogical control allowed to reveal some violations of the adaptive mechanisms of the cardiovascular system, which once again confirms the possibility of using the data of heart rate, blood pressure, Cooper's test for studying and analyzing the physical state of health and the degree of physical preparedness, as well as forecasting the health status of veterans sports.